Causal Link between Liberia’s Rice Imports and Income Changes - Billy, Abraham; Bonabana-Wabbi, Jackline; Lapaka Odong, Thomas (Agricultural and Environmental Sciences, 2018)
Liberia’s inability to produce enough rice to feed its population has led to massive rice imports, a high import bill, a negative balance of payment, vulnerability to shock and political instability (such as the 1979 rice riot that degenerated into civil unrest and the current economic crisis), increased food insecurity and high rate of poverty, among other effects. However, the effect of these massive rice importations on the national income has not been established. This provoked the need to determine the casual link between the imported rice volumes and income. To achieve this, the study models secondary annual time series data on Liberia’s agriculture subsector from 1979 to 2011. The Johansen cointegration technique, Error Correction Model (ECM) and the Granger Causality tests are used to determine the causal link between rice imports and income changes. Liberia’s imported rice volumes are observed to be sensitive to income changes in both the short-run and long-run periods. Based on the causation between imported rice volumes and income changes, this study recommends that the domestic rice production be improved and commercialized.
Keywords: Rice; Liberia; Income; Causality